Analisis Faktor-Faktor yang Memengaruhi Kualitas Layanan di Bioskop XXI Lotte Bintaro Menggunakan Service Quality - Fahira Adya Prasetyo; Widya Fitriani; Muhammad Fadli Rifki (Universitas Bunda Mulia, 2020)
This study aims to determine which service quality must be maintained or which quality should be improved by a product or service company. In this study, we use several service theories, service quality, service quality from a variety of expert opinions and the method we use in this study is the Service Quality (Servqual) method which has five dimensions, namely reliability, responsiveness, assurance (assurance), empathy (empathy), and physical evidence (tangibles). The number of respondents in this study is Jabodetabek residents who have visited and used products and services from Cinema XXI under the auspices of PT Nusantara Sejahtera Raya and located at Lotte Bintaro Mall. After distributing questionnaires and getting questionnaire data with 38 respondents, the next step is processing data by the Servqual method. This method begins by calculating the gap/difference between customer expectations regarding services with the reality of service perceived by customers. This was done by distributing questionnaires through social media. The company does not only focus on film services but also on food and beverage products. The results showed that all dimensions of servqual have negative values, so to improve customer satisfaction, it is recommended that company management can improve service quality in five dimensions of servqual. The attribute that has the biggest negative value is